Polymorphism in the GH1-Pstl gene associated to corporal characteristics in Nile tilapia strains - Blanck, Danielly Veloso; Gasparino, Eliane; Ribeiro, Ricardo Pereira; Marques, Débora Sommer (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this study was to determine the association of polymorphisms in the growth hormone gene GH1 with the corporal characteristics in Nile tilapia (Oreochromis niloticus) strains. Fragments of the caudal fin were collected from 5-month old fishes for analysis by polymerase chain reaction - restriction fragment length polymorphism (PCR-RFLP). The following measurements were accomplished: total length, standard length, height, width, and head length. A fragment with 652 bp of the GH1 gene was amplified with subsequent restriction with the enzyme PstI. For the analysis of the association of the molecular marker with the quantitative traits the SAS GLM procedure was used. The polymorphism described for the intron 1 of the GH1 gene of Nile tilapia had significant correlation with total length, standard length, and body height and width. It was found that the genotype PstI+/- is associated with better performance regardless of strain. Such association may be due to direct effect of the GH gene own regulation.